2018
DOI: 10.3168/jds.2017-13246
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association studies to identify quantitative trait loci affecting milk production traits in water buffalo

Abstract: Water buffalo is the second largest resource of milk supply around the world, and it is well known for its distinctive milk quality in terms of fat, protein, lactose, vitamin, and mineral contents. Understanding the genetic architecture of milk production traits is important for future improvement by the buffalo breeding industry. The advance of genome-wide association studies (GWAS) provides an opportunity to identify potential genetic variants affecting important economical traits. In the present study, GWAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 54 publications
(68 reference statements)
1
83
0
Order By: Relevance
“…These investigations also suggested that sex chromosome data should be included in GWASs to avoid missing important information and that animals carrying specific alleles could be used in selection plans to improve production traits, particularly milk fat yield or milk protein percentage . Liu et al (2018), in particular, identified one region containing the candidate genes MFSD14A, SLC35A3 and PALMD affecting fat and protein content, whereas a second region harbouring RGS22 and VPS13B candidate genes affected milk, fat and protein yields. Interestingly, the corresponding regions located on chromosomes BTA3 and BTA14 in the cattle genome were reported to harbour QTL influencing milk performance in dairy cattle (Harder et al 2006;Wibowo et al 2008), but the comparative analysis of the allelic variants involved in cattle and in buffalo suggested that, despite the similarities in genome arrangement, the variants associated with production traits could be different between the two species, particularly those affecting fat production (de Camargo et al 2015;Liu et al 2018).…”
Section: Gwassmentioning
confidence: 98%
See 4 more Smart Citations
“…These investigations also suggested that sex chromosome data should be included in GWASs to avoid missing important information and that animals carrying specific alleles could be used in selection plans to improve production traits, particularly milk fat yield or milk protein percentage . Liu et al (2018), in particular, identified one region containing the candidate genes MFSD14A, SLC35A3 and PALMD affecting fat and protein content, whereas a second region harbouring RGS22 and VPS13B candidate genes affected milk, fat and protein yields. Interestingly, the corresponding regions located on chromosomes BTA3 and BTA14 in the cattle genome were reported to harbour QTL influencing milk performance in dairy cattle (Harder et al 2006;Wibowo et al 2008), but the comparative analysis of the allelic variants involved in cattle and in buffalo suggested that, despite the similarities in genome arrangement, the variants associated with production traits could be different between the two species, particularly those affecting fat production (de Camargo et al 2015;Liu et al 2018).…”
Section: Gwassmentioning
confidence: 98%
“…Based on the SNPs involved in significant associations, candidate genes that were either trait‐specific or with pleiotropic effects could be identified. These investigations also suggested that sex chromosome data should be included in GWASs to avoid missing important information and that animals carrying specific alleles could be used in selection plans to improve production traits, particularly milk fat yield or milk protein percentage (Liu et al ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations